ANALISIS DAYA SAING DAN FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR KOPI INDONESIA KE PASAR JERMAN - Kedoh, Christian Adiputra; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 11 (2021): VOL 10 NO 11, NOVEMBER 2021 [4406 - 4562], 2021)
Indonesia is fourth largest coffee exporting in the world. Indonesian coffee has own characteristics can compete in global market. The purpose of this study was to analyze the market share and competitiveness of Indonesian coffee in the German market and to analyze the effects of international prices, production and exchange rates on Indonesian coffee exports to the German market. In this study, data collection used non-behavioral observation methods with data analysis techniques CMSA, RCA, and Multiple Linear Regression. Based on the analysis using the CSMA method, the market share seen for the Indonesian coffee commodity is quite good in German market. It can be seen from the calculation results on the effect of market composition and the effect of market distribution is positive. In terms of competitiveness, Indonesian coffee is to be strong where RCA value in all periods is more than one. International prices, production and exchange rates to simultaneously influence the decline and increase in coffee exports. International prices partially have positive significant effect on coffee exports. Production partially has positive significant effect on coffee exports. Exchange rates partially have a negative significant effect on coffee exports. Keywords: Indonesian Coffee, International Prices, Production, Exchange Rates, RCA, CMSA